Polyvinylalcohol-carbazate mitigates acute lung injury caused by hydrochloric acid - Dong, Caijuan; Liu, Jielu; Quaranta, Alessandro; Jing, Xu; Nie, Mu; Wheelock, Craig E.; Murrell, Benjamin; Coquet, Jonathan M.; Bowden, Tim Melander; Engstrand, Thomas; Adner, Mikael (Frontiers in Pharmacology, 2024)
Background: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are important causes of morbidity and mortality in critically ill patients. Gastric contents aspiration is one of the most common causes of ALI/ARDS. To date, there are still no specific and effective pharmacological treatments for ALI/ARDS. Polyvinylalcoholcarbazate (PVAC), a polymer that can bind endogenous aldehydes, neutralize oxidative stress and inhibit inflammatory factors, may be a potential treatment for ALI/ARDS. Methods: A hydrochloric acid (HCl) induced mouse model was employed to assess the effect of PVAC. The changes of lung mechanics, pulmonary edema, histology and immune cells, cytokines, and lipid mediators in bronchioalveolar lavage fluid (BALF) were investigated in HCl-challenged mice.In the HCl model, PVAC administration alleviated airway hyperresponsiveness and improved pulmonary edema and damage. In addition, it decreased the recruitment of neutrophils to the lung, and inhibited the increase of IL-6, TNF-α and leukotriene B4.Conclusions: These data indicates that PVAC is a potential candidate for the treatment of ALI/ARDS induced by aspiration of gastric acid or for the control of "asthma-like" symptoms in patients with gastroesophageal reflux.